Adolescent Mycardial Infarction with Normal Coronary Artery: A Case Report - Malik, FN; Ahmed, MN; Ahmed, N; Badiuzzaman, M; Dutta, AK; Banik, D; Rahman, MH; Huq, TS; Kabiruzzaman, M; Rashid, TBA; Kalimuddin, M; Ahmed, S; et al. (Journal of Armed Forces Medical College, Bangladesh, 2010)
Acute myocardial infarction may occur in adolescent with angiographically normal or near normal coronary arteries but the pathophysiology remain unclear. This mechanism includes in situ thrombosis or embolization with subsequent clot lysis and recanalization and vascular endothelial dysfunction, per se or combined. An one adolescent male having acute myocardial infarction (inferior with posterior with right ventricular infarction) was reported with no anomalous coronary artery nor history of risk factors for coronary artery disease and no history of drug abuse. He was thrombolysed in addition to per oral clopidegrol (600mg) and aspirin (300 mg) and other conventional anti-ischemic treatment. Two hours later the patient was pain free and there was complete resolution of ST segment. Five days later he was scheduled for coronary angiography. Key words: Adolescent myocardial infarction, coronary artery. DOI: 10.3329/jafmc.v5i2.4583 JAFMC Bangladesh Vol.5(2) (December) 2009, pp.40-43